Government policies on job satisfaction of radiographers in tertiary hospitals, Gauteng - Thandokuhle E. Khoza (AOSIS, 2024)
Background: The National Department of Health has different operational policies to monitor the performance of its employees and to reward them accordingly. These policies could have a direct bearing on job satisfaction and career advancement for radiographers employed by the public sector, as there are previous reports that show that these policies affect the job satisfaction of other healthcare professionals negatively. Aim: The aim of the study was to explore the influence of government policies on the job satisfaction of radiographers employed by public tertiary hospitals in the Gauteng province. Setting: The study was conducted in two public tertiary hospitals in the Gauteng province. Methods: The study used a primary exploratory qualitative research design, with a purposive sampling technique. Data were collected through individual and focus group interviews. The researcher recorded and transcribed the interviews. Thematic analysis was used to analyse the data. Results: Three government policies had a negative impact on job satisfaction for radiographers. These were the Occupational Specific Dispensation (OSD), the Performance Management and Development System (PMDS) and the Employment Equity Act (EEA). The failure to effectively implement these policies also had a negative bearing on career pathing. Conclusion: The implementation and structure of these three government policies have resulted in job dissatisfaction amongst radiographers employed by public tertiary hospitals and reduced the structure of career pathing. Contribution: The study highlighted three government policies that negatively affect job satisfaction in Gauteng.